(3fRgI GdMOGFb aj cjajI UfYI GdCdI GdeSeGI HWHb GdefGWbs - (3ZjGK GdOjf LeTjO cGTGfis; (3UGYO Hf GdMSf Hf YjSi GdQHYj GdHZOGOj, CHh GdYdGA,J (B417 (3g` s ((3YHO Gddg Ph Gdeff GHf GHh GdaVd Hf eXaQ GHh GdMSf GdJHQjRi GdTLGYi s)
(3ChdgG (B:s
(3GdMeO ddg GdPi LYd GWHGb GdSehGJ OGFQI hHYO jbhd SCdfi HYV GdGNhGf gd jecf Yed BdI jYQa efgG JbGhje GdchGcH hYQhVgG s
(3BNQgG (B:s
(3bGd di GdGNhGf hGdNdGf Gf GSec LeTjO hGdChdi Gf jchf GSe gPg GdGdI HMGe LeTjO s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B186 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B318s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1941s
Keywords: (3Gdadcs